A Propeller Flap for Single-Stage Nose Reconstruction in Selected Patients: Supratrochlear Artery Axial Propeller Flap - Cordova, Adriana; D'Arpa, Salvatore; Massimiliano, Tripoli; Toia, Francesca; Moschella, Francesco (Facial Plastic Surgery, 2014)
The paramedian forehead flap is the gold standard technique for nose reconstruction. It requires two different surgical operations which prolonged the postoperative dressing and care. We present our 5-year experience with a propeller flap based on the supratrochlear artery, which allows one-stage transfer of the forehead skin to the nose without the need for pedicle division. This technique is indicated in a selected group of patients who are not suitable for multiple-stage reconstructions because they have concurrent medical conditions, reduced mobility, or live far away from specialized medical centers. We have renamed this procedure as supratrochlear artery axial propeller flap, from the acronym STAAP flap, to stress the axial, well known and constant, vascularization of the flap. In the past 5 years, we have been performing 25 STAAP flaps; full-thickness nasal reconstruction was performed in 11 cases. The patients were 16 males and 9 females, with a mean age of 79.5 years. All patients had multiple comorbidities. Complete flap survival was observed in 23 cases and healing was complete in 7 days. In two cases, there was a partial distal necrosis of the flap treated conservatively. Cosmetic results were good and the patient's satisfaction was significant. These results indicate that the STAAP flap is a reliable and useful technique in selected cases, as old or noncompliant patients who benefit from a one-stage technique of nose reconstruction.
Keywords: nose reconstruction; propeller flap; forehead flap; supratrochlear artery